THE EFFECT OF TEA DWAGES AND EM4 IN MANUFACTURING FERTILIZER FOR THE GROWTH OF CAYYEY CHILLI - Jefri, Muhammad; Rihayat, Teuku; Fachraniah, F (Jurnal Sains dan Teknologi Reaksi, 2023)
Good quality organic fertilizer is useful for improving and maintaining soil fertility. In its application, this organic fertilizer is generally given through the soil but can also be given through the leaves. This research aims to determine the effect of tea dregs and the effect of the amount of EM4 on the growth of cayenne pepper, the results of stem height growth in cayenne pepper plants (Capsicum frutetences. L) by administration of EM4 and Tea Dregs with doses of 5;10;15;20;25 ml and Tea Dregs 50;100;150;200;250 and 250 grams have different characteristics, based on the statistical data it states the differences in dosages of the variables. 2, namely 10 ml/ 250 grams of tea dregs, dominates the growth of stem height in cayenne pepper plants.Keywords: Brown Sugar, Husk Charcoal,Cow Dung,The Dregs, EM4, Yellow Soil.